EFEKTIVITAS MODEL PEMBELAJARAN KOOPERATIF TIPE THINK TALK WRITE (TTW) BERBANTUAN MEDIA DIORAMA DALAM PEMBELAJARAN IPAS TERHADAP HASIL BELAJAR PESERTA DIDIK KELAS V DI SD GMIT 027 MEBUNG - Sufwinda Blegur; Petrus Mau Tellu Dony; Triznawasti Y. Daik (STKIP Subang, 2026)
This research was motivated by the low learning outcomes of Natural and Social Science (IPAS) for fifth-grade students at SD GMIT 027 Mebung, as teachers had not used varied learning models and media. Out of 21 students, only 6 achieved the KKTP score of 75, while the remaining 15 did not. The purpose of this research was to determine the effectiveness of the Cooperative Think Talk Write (TTW) learning model assisted by diorama media in IPAS learning on the learning outcomes of fifth-grade students at SD GMIT 027 Mebung. This study used a pre-experimental method with a quantitative research approach using a one-group pretest-posttest design. The research sample consisted of 21 students selected using a saturated sampling technique. The research instrument was a test with material validation of 90.00, diorama media validation of 98.66, and reliability of 0.77. Data analysis used a paired sample t-test with SPSS 22. The results showed tₕᴵₜ = 11.038 and tₜₐᵇ = 1.721, meaning tₕᴵₜ > tₜₐᵇ, thus H₀ was rejected and H₁ was accepted. The average pretest score of 54.95 increased to 87.95 in the posttest. Therefore, the Cooperative Think Talk Write (TTW) learning model assisted by diorama media was proven effective in improving student learning outcomes on the Food Chain of Rice Field Ecosystem material at SD GMIT 027 Mebung. Keywords: Cooperative Type Think Talk Write, Diorama Media, IPAS, Learning Outcomes, Elementary School